Assessment of knowledge and challenges toward the use of subcutaneous self-injecting insulin among diabetes patients during COVID-19 pandemic in Saudi Arabia - Samar Zuhair Alshawwa; Sarah Abdulaziz Almass; Sara Abdullah Alotaibi; Injood Mnwer Almutairi; Amjad Yhaya Otain; Amal Hassan Al-Najjar; Nada Benajiba (Elsevier, 2021)
Background: The COVID-19 pandemic has revolutionized the delivery of chronic health care. For diabetic patients, maintaining regular contact with healthcare providers and visiting healthcare centers are crucial to patients' overall ability to control their glycemic status. Objective: To assess patients' knowledge regarding the use of insulin injection devices and the challenges these patients face in obtaining medical advice, as well as to suggest alternative solutions for addressing these challenges among diabetic patients self-administering their injections during the COVID-19 pandemic. Methodology: An observational cross-sectional study was conducted among a sample population (N = 178) of diabetic patients attending Security Forces Hospital-Riyadh, Saudi Arabia, from which the Institutional Review Board (IRB) was granted. Data was collected using a self-administered questionnaire, which was distributed from August to September 2020. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) program (version 21). Significant P-value = < 0.05. Results: The majority of patients had good knowledge and practice explained with values 73.6% of total papulation. Sixty-four percent of patients with type 1 diabetes and 59% of patients with type 2 diabetes reported experiencing moderately severe challenges obtaining counseling. There was no correlation between severity of disease and knowledge levels (p-value = 0.36). The most appropriate means of obtaining counseling was determined to be conversations with healthcare providers; this strategy received an overall average score of 4.9 ± 0.4 (p-value < 0.0001). Conclusion: Regardless of whether knowledge is high among patients with diabetes, continuous support and counseling from healthcare providers is critical. The creation of innovative approaches to facilitate communication between diabetes patients and healthcare providers is recommended for continued patient care during the COVID-19 pandemic.